The Little Data Book on Africa 2012/2013 - WorldBank (World Bank, 2015)
The Little Data Book on Africa 2012/2013 is a pocket edition of Africa Development Indicators 2012/2013. It contains some 115 key indicators on economics, human development, governance, and partnership and is intended as a quick reference for users of the Africa Development Indicators 2010 book and African Development Indicators Online. The country tables present the latest available data for World Bank member countries in Sub-Saharan Africa, covering about 1,700 indicators from 1961 to 2011. Key themes are: ? Basic indicators ? Drivers of growth ? Participating in growth ? Capable states ? Partnerships Designed to provide all those interested in Africa with quick reference and a reliable set of data to monitor development programs and aid flows in the region, this is an invaluable pocket edition reference tool for analysts and policy makers who want a better understanding of the economic and social developments occurring in Africa. For free access to Africa Development Indicators online, please visit http://data.worldbank.org/data-catalog.